2011
DOI: 10.1007/s10620-010-1523-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibodies to Mycobacterium avium Subspecies paratuberculosis Combined with Anti-Saccharomyces cerevisiae Antibodies in Crohn’s Disease Patients: Prevalence and Diagnostic Role

Abstract: Our results suggest a complementary role of ASCA and anti-MAP for CD diagnosis and a possible common role of bacteria in small intestinal mucosal damage in CD and coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…20-25 In our former study, 90% of celiac disease patients had positive serological responses towards one or more of these microbial markers. 20 The present study showed for a first time that similar serological responses can be detected already in the early stages of celiac disease when the mucosal villi are still morphologically normal.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…20-25 In our former study, 90% of celiac disease patients had positive serological responses towards one or more of these microbial markers. 20 The present study showed for a first time that similar serological responses can be detected already in the early stages of celiac disease when the mucosal villi are still morphologically normal.…”
Section: Discussionmentioning
confidence: 78%
“…It has been shown that seroreactivity against the Saccharomyces cerevisiae (ASCA), Pseudomonas fluorescens-associated sequence (I2) and Bacteroides caccae TonB-linked outer membrane protein (OmpW) can be detected in overt celiac disease (so-called Marsh III lesion). 20-25 Positive seroreactivity towards ASCA has also been found in the first-degree relatives of celiac disease patients. 26 Furthermore, the serum titers of these microbial seromarkers may decrease after initiation of gluten-free diet.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, ASCA cross react with anti-mycobacteria response [48], [49]. However, ASCA are not specific for CD disease as they can also be detected in ACD [50], [51]. Anti-L5P antibodies may thus represent a valuable specific serological marker for CD as anti-L5P IgG titers were not increased in ACD or UC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, C albicans also express common β‐glucan epitopes similar to that of S cerevisiae , suggesting that ASCA as a diagnostic tool may not be specific enough to detect individual fungi . Various sources of microbes and receptors that express these ubiquitous epitopes might also affect ASCA affinity binding, including mycobacteria M paratuberculosis and the fimH receptor on GP2 on M cells, all of which likely contain the mannose alpha 1,3 mannose epitope for ASCA . When serological markers are considered individually, ASCA has the best combined sensitivity and specificity for CD; and pANCA for UC.…”
Section: Impact Of Fungal Alterations On Ibd Diagnosis and Disease Acmentioning
confidence: 99%